Botulinum Toxin A Injection in the Bladder Neck: A Promising Treatment for Urinary Retention - Marianne Alam; Joseph Zgheib; Mohamad-Fadi Dalati; Fouad El Khoury (Case Reports in Urology)
Secondary to failure of optimal medical therapy and the high morbidity that accompanies surgical techniques in high risk patients, the use of de novo treatments including botulinum toxin A is emerging in the treatment of benign prostatic hyperplasia (BPH). However, the treatment of urinary retention secondary to BPH via injecting botulinum toxin into the bladder neck is not well established in the literature. This case report describes the case of a 75-year-old male patient with a chronic history of obstructive lower urinary tract symptoms (LUTS) and multiple comorbidities who was admitted to the hospital for management of recurrent urinary retention. The patient was not a surgical candidate for transurethral incision of the prostate (TUIP) or transurethral resection of the prostate (TURP). Botulinum toxin injection into the bladder neck was performed with very satisfying results. Botulinum toxin injection in the bladder neck presents a promising minimally invasive, tolerated, and cost-effective approach for the treatment of urinary retention in patients with benign prostatic obstruction who are not candidates for surgery or in whom medical treatment has failed. More research is needed to identify the efficacy of this novel approach.